Contribution of advanced training for real problem solutions within sustainable development goals: the case of an e-learning PhD - Oliveira, Carla Padrel de (2020)
In this work, we intend to evaluate the contribution of this e-learning PhD program on Social Sustainability and Development for worldwide real problem solutions, in particular related with the achievement of the Sustainable Development Goals (SDG). The research was conducted for those research plans submitted between 2014 and 2016. A content analysis was applied to those students’ research plans.